A male child with Van Wyk-Grumbach syndrome and hypertrophic cardiomyopathy: a rare case with a rare association - Zabeen, Fahmida; Nazrin, Tahera; Begum, Noorjahan (BIRDEM Medical Journal, 2022)
Children with severe long-standing hypothyroidism rarely present with Van Wyk–Grumbach syndrome with delayed bone age and pseudoprecocious puberty. Till date, very few such cases are reported in boys. Boys are characterized by testicular enlargement with minimal penile enlargement. The prepubertal response in this syndrome is always isosexual and is mediated by very high thyroid-stimulating hormone levels acting through the follicle-stimulating hormone receptors. Although, hypothyroidism-induced dilated cardiomyopathy is an uncommon phenomenon, here we present a case of Van Wyk–Grumbach syndrome in a prepubertal boy with hypertrophic cardiomyopathy BIRDEM Med J 2022; 12(3): 226-229